Bibliography of the published and unpublished work of the regional programme of monetary studies 1968-1987 - Stewart, June (ISER St AugustineTT, 1988)
Compiles research reports, speeches, papers presented at annual conferences, mainly by Caribbean economists. Contains 3 sections. The first is arranged alphabetically by author, with abstracts and keywords. Section 2 contains a conference index and section 3, an alphabetical subject index.